Ukama Ustawi Baseline Survey Report for Zambia - Kimenju, Simon; Kamau, Philip; Adam, Rahma (2023)
A baseline survey for Zambia was undertaken November 2022. A total of 705 households were interviewed in this survey from 7th to 19th November, in 8 camps within 5 districts in Southern and Eastern provinces. These sites are earmarked for intervention by the UU initiative. The questionnaire focused on the October 2021-May 2022 rainy season targeting 5 main crops. The baseline report summarizes the main descriptive findings of the analysis of this baseline data. The study was led by WorldFish, and it was done in partnership with Kula Vyema Center of Food Economics and BrandComm Ltd Zambia.